CHILDREN CREATE EMOTIONAL PLACES (THE HUT). DESIGN PRACTICES IN RELATIONAL, EXPERIENTIAL AND ECOSOMATIC PEDAGOGICAL APPROACHES, IN RESPONSE TO THE CONTEMPORARY SCHOOL MINDSET - Kokkinaki, Katerina; Zoe Georgiadou (Design/Arts/Culture, 2025)
In this article it is argued that the lack of proximity to the school environment and learning hinders the holistic development of children. What is missing in contemporary learning is the development of children relationships with the emotional, social and environmental world and most importantly with themselves. Community build-up is deemed essential in this research for collaboration, active engagement and participatory planning in an everyday learning context. Collaboration within the community is intended to improve the children’s daily lives and not simply to improve their performance in a learning subject outside their own interests and culture. In this way, children are actively and spontaneously involved in the events that they themselves create. The experiential situations stem from children everyday life, generating intense emotion, a key feature for their all-round development. Children experiences are formed in a playful, multimodal, open and interactive field with the community. In this research a holistic scheme of work is approached, with intensive experiential activity, creative play in nature, kinesthetic action, and ecosomatic perception. At the same time, by intervening experientially and participatively in the natural landscape of the school, students through ecosomatic pedagogy understand both the environmental and material cultures as a concept with permeabilities. In relational-experiential pedagogy, the interactive dynamics of persons (from the perspective of their emotional engagement) with their environment is important. Person and environment do not constitute two separate entities that interact but they rather constitute a single condition of existence in the world. Thus, the atmosphere of the school changes as children relate directly and intensely emotionally to individuals and the environment.